ANALISIS SISTEM PELAKSANAAN PENGHITUNGAN PAJAK ATAS KENDARAAN BERMOTOR DALAM MENINGKATKAN PAJAK DAERAH DI KANTOR SAMSAT GUNUNG SITOLI - Maria Magdalena Bate (Jurnal Akuntansi Bisnis dan Ekonomi, 2018)
Motor Vehicle Tax (PKB) is the implementation of regional taxes on motorized vehicles. The object of motor vehicle tax is proof of ownership or power of motorized vehicles, while the subject of motorized taxation is an individual or entity that owns or controls a motorized vehicle. The purpose of this study is to find out the system of implementation of Roda 2 motor vehicle tax (PKB) at the Office of the Gunungsitoli Single Roof Single Administration System (SAMSAT). The type of research in this study uses a type of qualitative descriptive research with data collection techniques of observation and interviews. From the results of the study it is known that the calculation of Wheel 2 PKB in Gunungsitoli City Samsat office has been carried out in accordance with taxation in Indonesia by referring to Law No. 28 of 2009 concerning Regional Taxes and Regional Retribution (PDRD) and also North Sumatra Provincial Regulation No. 1 of 2015 concerning Regional Tax of North Sumatra Province. In the Wheel 2 PKB Collection system at the Gunungsitoli SAMSAT office carried out with an Official Assessment System which means that tax collection is based on the decree of the Head of Region by using SKPD (Regional Tax Assessment Letter) and / or other similar documents in the form of tickets and calculation notes, stipulation by SAMSAT office officers, and the payment is made by the Taxpayer and deposited by the officer to the Bank, namely the Gunungsitoli Branch of North Sumatra Bank.